The Effect Of Job Description And Compensation On Employee Performance At PT Mettana, Bandung City - Ridlwan Muttaqin; Arie Hendra Saputro (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Abstract The purpose of this study is to ascertain how much of an impact Job Description and Compensation, either separately or together, have on Employee Performance. With a descriptive and verification strategy, this study employs quantitative approaches. 63 employees were sampled using the saturated sample technique. The outcomes of distributing questionnaires were used to determine data collection procedures. Descriptive analysis, multiple regression, correlation coefficient, determination coefficient, and hypothesis testing were all employed in data analysis. (t test and F test) using SPSS version 26. Employee Performance, Job Description, and Work Compensation all fell into the medium range, according to the findings. Employee Performance is positively impacted by Job Description and Compensation, according to the regression equation. According to preliminary research findings, compensation has no substantial impact on employee performance, whereas job description has a significant impact. Job descriptions and pay both have a big impact on employee performance simultaneously.